Understanding the social determinants of opioid related hospitalizations - Sanmartin, Claudia; Carriere, Gisele (International Journal of Population Data Science, 2018)
Introduction The current opioid crisis is recognized by governments at many levels as an urgent priority. While there is basic demographic information on who experiences opioid related adverse events, there is little information to provide a more fulsome profile of those experiencing these events for targeted intervention and forward projection estimation. Objectives and Approach This study is the first to use a nationally-representative Census of Population linked with health administrative data to examine opioid-related hospitalization patterns across income and Aboriginal status. Results Preliminary analyses using 2006 Census-hospital linked database found cohort rates of opioid-related hospitalizations are up to 7 times higher among Aboriginal youth, and also for young adults (12-19/ 20-24) compared with non-Aboriginal youth or young adults. Rates among these youth living on reserves were 8.4 times higher; among those off reserve 8.7 times higher. Rate among all youth living in lower income households was 5 times higher compared with those living in highest income households, For Aboriginal persons in lowest income quintile, the rate was 3 times higher relative to non-Aboriginal persons in same quintille. Conclusion/Implications New linked health data reveal new information regarding the profile of those who experienced opioid-related adverse events. This information will serve to inform targeted intervention strategies, models for forward estimation of events.